Distribution of rare earth elements in surface sediments of the western Gulf of Thailand: Constraints from sedimentology and mineralogy. (30th August 2019) - Liu, Shengfa; Zhang, Hui; Zhu, Aimei; Wang, Kunshan; Chen, Min-Te; Khokiattiwong, Somkiat; Kornkanitnan, Narumol; Shi, Xuefa
Abstract: To understand the modern sedimentation and land-sea interaction processes in the Asian margin seas, we analyze rare earth element contents (REE, i.e., La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu) and grain sizes, detrital minerals from 158 surface sediment samples collected from the western Gulf of Thailand (GoT). The results reveal that the REE contents ranged from 25.42 μg/g to 201.21 μg/g, with an average value of 137.21 μg/g, and that the GoT is characterized by higher accumulations of LREE relative to HREE, together with negative Eu anomalies. Based on the spatial distribution characteristics of REE contents, δCe and δEu, the western GoT can be classified into three geochemical provinces. The Province I covers the northern and northwestern coastal zones of the GoT, including the entire upper GoT; its coarse size fraction and distribution pattern of hornblende- and quartz-dominated minerals caused REE contents to be the lowest, and these sediments were mainly derived from the rivers around the upper GoT, including the Chao Praya River and the Kea Klong River. The Province II is located in the central GoT and has the highest REE concentrations due to finer sediment composition and higher contents of zircon, authigenic pyrite, and biogenetic limestone. The Province II has two accumulation centers around Samui Island and Koh Chang Island, with REE spatial distribution influenced by the seasonal setting and mixed derived from multiple provenances around the GoT. The Province Ш is located in the lower GoT, close to Malaysia. The sediment type in this region is similar to that of Province I except for different detrital mineral compositions, especially the presence of siderite that is responsible for higher REE contents. The sediments in this region exhibits similar distribution patterns to those of terrestrial materials from the Malaysian peninsula such as that from the Kelantan River. The transportation processes of sediments in this region are mainly controlled by the coastal current.